Cryogenic Equipment for Low-Temperature Hardening of Instruments and Machinery for Needs of Machine Building and Rolling Production - Zharkov, I.P. (Science and Innovation, 2024)
A temperature-controlled nitrogen cryostat with embedded high-temperature thermally insulated container holder of treated objects has been created for low-temperature hardening of instruments and machinery. To control the surface temperature of rolls a system for cryoblasting of rolls by nitrogen gas-fluid mixture has been designed.